2004
DOI: 10.1063/1.1737796
|View full text |Cite
|
Sign up to set email alerts
|

Local built-in potential on grain boundary of Cu(In,Ga)Se2 thin films

Abstract: We report on a direct measurement of two-dimensional potential distribution on the surface of photovoltaic Cu(In,Ga)Se2 thin films using a nanoscale electrical characterization of scanning Kelvin probe microscopy. The potential measurement reveals a higher surface potential or a smaller work function on grain boundaries of the film than on the grain surfaces. This demonstrates the existence of a local built-in potential on grain boundaries, and the grain boundary is positively charged. The local built-in poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
111
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(122 citation statements)
references
References 14 publications
(3 reference statements)
9
111
1
Order By: Relevance
“…The predicted valence band offset caused by the removal of copper atoms from the boundary leads to the formation of a neutral barrier for holes that do not otherwise impede the electron transport and reduce recombination [22]. The existence of this neutral barrier has been confirmed experimentally by several methods [10,[23][24][25]. In our case, microluminescence measurements based on spectrum imaging revealed a redshift of the emission spectrum at grain boundaries.…”
Section: Luminescence From Grain Boundariessupporting
confidence: 66%
“…The predicted valence band offset caused by the removal of copper atoms from the boundary leads to the formation of a neutral barrier for holes that do not otherwise impede the electron transport and reduce recombination [22]. The existence of this neutral barrier has been confirmed experimentally by several methods [10,[23][24][25]. In our case, microluminescence measurements based on spectrum imaging revealed a redshift of the emission spectrum at grain boundaries.…”
Section: Luminescence From Grain Boundariessupporting
confidence: 66%
“…Typical examples are the carefully engineered Cu deficient GBs in CIGS solar cells 23,24 and a high temperature CdCl2 treatment for CdTe solar cells 24,25 .…”
mentioning
confidence: 99%
“…KFM revealed that random GBs have negative influences on solar cell performance compared to those with low R values in polycrystalline Si, 27,28 and that the electron-hole pairs are well separated at GBs in high-efficiency CIGS solar cells. [29][30][31] According to our previous work on the potential variations around the GBs using KFM, 32 the potentials were higher at GBs by approximately 30 meV than those in the BaSi 2 grain interiors in the undoped n-type BaSi 2 films, suppressing the charge carrier recombination at the GBs. This explains the reason why the minority-carrier diffusion length (ca.10 lm) is much longer than the average grain size of undoped n-BaSi 2 (ca.0.2 lm), 8 which is to be an active layer in a BaSi 2 pn junction solar cell.…”
mentioning
confidence: 99%